2019
DOI: 10.1371/journal.pone.0209703
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization and vibratory synchronization transmission of a weakly damped far-resonance vibrating system

Abstract: The self-synchronization of rotors mounted on different vibrating bodies can be easily controlled by adjusting the coupling parameters. To reveal the synchronization characteristics of a weakly damped system with two rotors mounted on different vibrating bodies, we propose a simplified physical model. The topics described in this paper are related to coupling dynamic problems between two vibrating systems. Both synchronization and vibratory synchronization transmission of the system are studied. The coupling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Single mass body is studied in most of the above papers and two mass bodies are introduced below. Chen et al [14] proposed a model in which two ERs drive two masses respectively and discussed the coupling dynamics between two masses. Shishkin et al [15] designed the two masses vibration crusher with two ERs mounted on the outer mass.…”
Section: Introductionmentioning
confidence: 99%
“…Single mass body is studied in most of the above papers and two mass bodies are introduced below. Chen et al [14] proposed a model in which two ERs drive two masses respectively and discussed the coupling dynamics between two masses. Shishkin et al [15] designed the two masses vibration crusher with two ERs mounted on the outer mass.…”
Section: Introductionmentioning
confidence: 99%
“…With the maturity of synchronization technology, self-synchronization theory is gradually applied to engineering vibration machine. 1–9 Blekhman et al. proposed the self-synchronization theory of the double-exciter vibrating machine; the results showed that the mechanical structure is simplified, the maintenance workload is decreased, and the service life of the equipment is increased.…”
Section: Introductionmentioning
confidence: 99%